The Effect of Cooperative Learning Model Implementation on Student Learning Understanding On Thematic Learning in Elementary School Literature Studies: Pengaruh Penerapan Model Cooperative Learning Terhadap Pemahaman Belajar Siswa Pada Pembelajaran Tematik di Sekolah Dasar - Sonia Yulia Friska (Journal of Vocational Education and Information Technology (JVEIT), 2021)
This research is based on the lack of understanding of student learning in learning in primary schools. It is affected by the inappropriate use of teaching model, teaching management and the low of students’ critical thinking skills. The formulation of the problem in this study is what points that appear related to the effect of the applicaton of cooperative learning models on students understanding of learning in thematic learning based on previous studies.The type of research used by the researches was literature study, it examined 13 journals and 1 thesis. This study aims to find out what points that appear related to the effect of the application of cooperative learning models to the understanding of student learning in thematic learning based on previous studies. After studying 13 journals and 1 thesis, it was found that 3 points were made as a result of research, cooperative learning model can increase student cooperation in a study group, cooperative learning model can increase student communication skills, cooperative learning models can improve students’ learning achievement. Based on the 3 points above, the result of the study indicates that there is an influence of the application of the cooperative learning model towards students’ understanding of learning in the thematic learning in elementary schools.